Implementasi Kebijakan Automatic Adjustment Pada Operasional Satuan Kerja Pemasyarakatan di Lingkungan Kantor Wilayah Kementerian Hukum Dan Ham Bali - Juli Saptaputra Hantana; Ida Ayu Putu Sri Widnyani; Gede Wirata (Public Inspiration : Jurnal Administrasi Publik, 2024)
In the President's directive at the plenary cabinet meeting on November 17, 2021, it was stated that strategic steps need to be taken in 2022 to mitigate the continuing and worsening impact of the Covid-19 pandemic by reserving a 5% budget allocation (automatic adjustment) in each Ministry/Agency. This study aims to understand and analyze the processes, obstacles or constraints that arise, and their solutions in the implementation of the Automatic Adjustment policy in the operational work units of the Corrections Office within the Bali Regional Office of the Ministry of Law and Human Rights. This research is a qualitative study with a descriptive approach. Data and information collection in this study used observation, interviews, documentation studies, and online data searches. The results of the study indicate a lack of understanding of the purpose of implementing the policy, the absence of standards in the form of regulations or derivative rules that more specifically regulate policy implementation, the budgetary resources managed by the work units are insufficient for policy implementation, there are no SOPs/technical guidelines/implementation instructions in implementing the policy, and there is still minimal support from Echelon I or the Central Unit. The obstacles that arise include changes in activity implementation plans, delays in activities, difficulties in budget realization, and problems in achieving output targets, while solutions to overcome these include re-planning, budget revisions, synergy, and changes in activity implementation mechanisms.